Quantitative clinical adjustment analysis of posterior single implant crown in a chairside digital workflow: A randomized controlled trial. Issue 11 (20th August 2019) - Zhang, Yifan; Tian, Jiehua; Wei, Donghao; Di, Ping; Lin, Ye
Abstract: Objectives: To compare the three‐dimensional changes in quantity and morphology following clinical adjustment of a posterior single implant crown between chairside digital workflow (test) and hybrid digital workflow (control). Materials and Methods: A total of 33 participants were included for single‐tooth replacement with screw‐retained crowns in posterior sites of either the maxillary or mandible. A total of 17 participants were carried to a chairside digital workflow, receiving monolithic lithium disilicate (LS2)‐crowns (test), while the remaining 16 participants were fitted with CAD/CAM‐fabricated zirconia superstructures and hand‐layered ceramic veneering crowns (control). As each crown underwent intraoral scanning (3Shape TRIOS Color, 3Shape), 3D digital models were rendered. These scans were taken both before and after try‐in. Clinical adjustment dimensional changes were measured by superimposing the optical scans of models within a reverse software (Geomagic Control 2014). Adjustment counts and amounts (from vertical dimension) between two workflows were assessed and compared. Time consumption was recorded for efficiency analysis. Results: All patients were successfully treated in both groups. The median maximum vertical adjustment (taking both occlusal and interproximal surfaces into consideration) was 237 μm ± 112 in the test group and 485 μm ± 195 in the control group ( p  < .0001), respectively. The median adjustment count was 2.00 ± 1.09 in test group and 3.00 ± 1.05 in control group ( p  = .001), respectively. The total active working time/ total time for two workflows was 92.3/113.7 min for the test group and 146.3/676.3 min for the control group, respectively. Conclusion: The test group showed fewer adjustments and apparent precision on the occlusal surface compared with the control group with only a fifth of the consumption of a hybrid workflow.